Arterial hypertension in women in the menopausal period - Stachowiak, Grzegorz; Faflik, Urszula; Zając, Agnieszka; Stetkiewicz, Tomasz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2008)
Among cardiovascular diseases in women arterial hypertension is an extremely frequent and dangerous illness. The authors of this article present the pathogenesis of arterial hypertension, its possible complications, some therapeutic methods for enhanced blood pressure as well as the influence of exogenous sex hormones in the form of various contraceptive drugs and hormonal therapies (HT) of the menopausal period.